Systematic Literature Review: Penerapan Manajemen Keselamatan dan Kesehatan Kerja di Puskesmas - Firmansyah Kholiq Pradana PH (Health Science Udinus, 2023)
The research evaluates the implementation of Occupational Safety and Health (K3) in Indonesian Community Health Centers (Puskesmas), with a focus on risk management, standard preventive measures, and fatal work accidents. Despite efforts to implement an Occupational Safety and Health Management System (SMK3), research shows gaps in the understanding and awareness of Community Health Center officers regarding standard preventive measures. Fatal accidents, such as electric shocks and fires, highlight the need for holistic risk management. Recommendations include regular training, equipment maintenance, and ongoing evaluation to improve OSH practices in these health facilities. These measures support the quality of healthcare and patient safety. This research was conducted using a systematic literature review guided by the PICO Framework to formulate specific and focused research questions. This research shows that careful planning has a key role in the successful implementation of Occupational Safety and Health (K3) in Community Health Centers, with the use of technology such as web-based reporting systems to increase efficiency. Continuous evaluation is an important instrument for identifying successes and challenges in K3 implementation, while external involvement and support is needed to overcome internal and external obstacles. Constraints such as lack of resources are the main focus, but evaluation also opens up opportunities for improvement, especially in the implementation of K3 policies and procedures. Optimizing K3 planning strategies is the key to increasing compliance and effectiveness of K3 management at the Community Health Center level, with an expanded focus on continuous supervision and monitoring.